Influence of socioeconomic status on survival after primary aortic or mitral valve replacement. Issue 2 (4th May 2007) - Bagger, J P; Edwards, M-B; Taylor, K M
Abstract : Objectives: We sought to evaluate whether socioeconomic status influences outcome after first-time single aortic or mitral valve replacement. Setting: National Heart Valve registry. Design and Patients: Between 1 January 1986 and 31 December 2001, 51 844 consecutive patients who underwent primary aortic or mitral valve replacement were registered on the United Kingdom (UK) Heart Valve Registry. Data included age, gender, valve position, type of valve implant, postcode, follow-up time, date and cause of death. The Carstairs deprivation score (1991 Census data for the UK) was used to stratify cases by level of social deprivation according to postcodes. Results: Both 30-day and 1-year survival/mortality rates were similar across all socioeconomic levels. However, long-term survival rate (up to 15 years) was significantly higher in the least deprived socioeconomic level than in the two most deprived levels. There was an 18% lower survival rate amongst women in the most deprived levels (35.9%, 95% CI: 32.4 to 39.4) versus the least deprived level (43.7%, 95% CI: 38.1 to 49.2, p<0.004). In men, survival in the most deprived levels (39.5%, 95% CI: 36.4 to 42.5) was 7% lower than in the least deprived level (42.7%, 95% CI: 37.7 to 47.7, p<0.005). Biological valve, mitral position, female gender, and low socioeconomic status were all associated with long-term mortality. Conclusions: A disadvantaged social background has a negative influence on long-term survival after aortic or mitral valve replacement, especially among women.